ANALISIS PERAMALAN PENJUALAN PRODUK TELUR UNTUK MENENTUKAN PERSEDIAAN PADA CV. MONALISA MITRA MAKMUR KOTA GUNUNGSOLI - Agusnama Giawa; Sophia Kakisina; Aferiaman Telaumbanua; Heniwati Gulo (Lembaga Pengembangan Kinerja Dosen, 2026)
Sales forecasting is an important aspect of inventory management, especially for products with a limited shelf life such as eggs. Inaccurate demand estimation can lead to excess inventory resulting in losses or insufficient stock that causes missed sales opportunities. This study aims to analyze egg sales patterns and examine the importance of implementing sales forecasting as a basis for inventory management at CV. Monalisa Mitra Makmur, Gunungsitoli City. The data used in this study consist of egg sales data from 2023 and 2024. The results of the analysis show that egg sales experienced significant fluctuations due to seasonal factors, changes in economic conditions, and religious holiday periods. Sales in 2024 showed a substantial decline compared to 2023, indicating challenges in inventory planning. The main problems faced by the company are unstable demand patterns and limitations in utilizing historical sales data as a forecasting basis. Therefore, the implementation of appropriate sales forecasting methods is expected to help the company determine optimal inventory levels, minimize the risk of losses, and improve operational efficiency and competitiveness.